IMAGES OF NATIONAL IDENTITY AND CULTURAL INTEGRATION IN CONTEMPORARY UZBEK AND KARAKALPAK LITERATURE (BASED ON MEDIA SOURCES ANALYSIS) - Aytmuratova Gulchehra Bahadir qizi; Tog`ayeva Gulandom Jummayevna (Modern American Journals, 2025)
This article explores the representation of national identity and cultural integration in contemporary Uzbek and Karakalpak literature through the lens of modern media discourse. In the context of globalization and evolving cultural communication, literature serves not only as an aesthetic expression but also as a platform for negotiating ethnic memory, collective belonging and intercultural harmony. Uzbek and Karakalpak authors actively engage with themes of historical inheritance, language preservation, interethnic coexistence and the transformation of traditional values under modern socio-political influences. Special attention is given to how literary works reflect the dynamics of cultural dialogue, East–West identity intersections and the construction of a shared yet diverse cultural space in the Central Asian region. The study relies on an analytical review of printed and digital media materials that document literary discussions, author interviews, cultural forums and public debates, revealing how national self-awareness is reaffirmed not in isolation but through cultural interaction. The research highlights that contemporary literature increasingly portrays identity not as a static category, but as a living, flexible and integrative phenomenon shaped by media-mediated cultural exchange.
Keywords: National identity, cultural integration, modern Uzbek literature, Karakalpak literature, media discourse, ethnic memory, intercultural dialogue.